2004
DOI: 10.1128/aac.48.6.2223-2227.2004
|View full text |Cite
|
Sign up to set email alerts
|

Clade-Specific Flucytosine Resistance Is Due to a Single Nucleotide Change in the FUR1 Gene of Candida albicans

Abstract: Population studies have indicated that natural resistance to flucytosine (5FC) in Candida albicans is limited to one of the five major clades, clade I. In addition, while 73% of clade I isolates are less susceptible to 5FC (MIC > 0.5 g/ml), only 2% of non-clade I isolates are less susceptible. In order to determine the genetic basis for this clade-specific resistance, we sequenced two genes involved in the metabolism of 5FC that had previously been linked to resistance (cytosine deaminase and uracil phosphorib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
88
2
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 26 publications
(45 reference statements)
7
88
2
1
Order By: Relevance
“…C. parapsilosis showed 3.4% resistance to itraconazole, while it showed 50% resistance in the present study. FUR 1 gene detection in 5FC resistant isolates correlated with findings of studies of Dodgson et al, [6] Hope et al, [20] and Pujol et al, [21].…”
Section: Prevalencesupporting
confidence: 83%
See 1 more Smart Citation
“…C. parapsilosis showed 3.4% resistance to itraconazole, while it showed 50% resistance in the present study. FUR 1 gene detection in 5FC resistant isolates correlated with findings of studies of Dodgson et al, [6] Hope et al, [20] and Pujol et al, [21].…”
Section: Prevalencesupporting
confidence: 83%
“…However, large scale studies have shown primary resistance to C.albicans to be in the range of 3-6.5% [5]. Primary resistance to 5-flucytosine (5FC) occurs by decreased activity of either cytosine deaminase or UPRTase due to mutations in the genes, FCY1 or FUR1 [6,7].The study of Dodgson AR et al, showed single mutation at position 301 in FUR1 gene, responsible for 5FC resistance in C.albicans. In the present study, an attempt was made to detect the presence of mutant FUR1 gene in 5FC resistant Candida spp.…”
Section: Introductionmentioning
confidence: 99%
“…While antifungal resistance has been demonstrated to occur more frequently among clade II and clade SA isolates [20,21], conclusive evidence has yet to emerge of hyper-virulent strains through the use of accepted DNA fingerprinting techniques with high discriminatory power [22].…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in the cytosine deaminase gene FCY1 (named FCA1 gene in C. albicans) or cytosine permease gene FCY2, which may result in the poor uptake of drug, are the most common causes of drug resistance (23,24). Primary resistance to 5-FC may also occur due to decreased activity of either cytosine deaminase or uracil phosphoribosyltransferase (UPRTase) as a result of mutations in the genes FCY1 or FUR1 (16,21,25,26). A recent research on gene FCA1 suggested that the presence of a Ser29Leu substitution in Fca1p in C. dubliniensis isolates is responsible for clade-specific resistance to 5-FC (27).…”
Section: Discussionmentioning
confidence: 99%
“…Amplification and sequencing of 5-FC resistanceassociated genes (FUR1, code for uracil phosphoribosyltransferase, and FCA1, code for cytosine deaminase) were also performed using a procedure described previously (16). The sequences of the two isolates were compared with the reference strain SC5314.…”
Section: Molecular Analysismentioning
confidence: 99%